Ce3+‐Doped Yttrium Aluminum Garnet Transparent Ceramics for High‐Resolution X‐Ray Imaging. Issue 6 (30th January 2022) - Ji, Tao; Wang, Ting; Li, Hao; Peng, Qingpeng; Tang, Haitao; Hu, Song; Yakovlev, Alexey; Zhong, Yang; Xu, Xuhui
Abstract: Scintillators, as the core materials for X‐ray imaging, have received great attention in radiation detection, security inspection, and biomedical applications. However, the current single crystal and thin film scintillators have encountered several issues, such as high cost, insufficient stability, and uneven distribution, which undoubtedly limit the development of high‐quality X‐ray imaging. Herein, the Y3 Al5 O12 :Ce 3+ (YAG:Ce 3+ ) transparent ceramics (TCs), which presented a high transmittance of 82% and a steady‐state light yield of 24 600 photons MeV −1, are prepared by the vacuum solid‐state reactive sintering method. The fabricated YAG:Ce 3+ TCs exhibit X‐ray imaging with an excellent spatial resolution (≈34.7 lp mm −1 ). Moreover, because of the structural stability of YAG:Ce 3+ TCs, long‐term stable work under X‐ray irradiation is realized successfully. This work indicates that the TC scintillators provide a new opportunity for the development of high‐quality X‐ray imaging. Abstract : Herein, a high‐resolution X‐ray imaging of more than 20 lp mm −1 is achieved through the Y3 Al5 O12 :Ce 3+ transparent ceramics with high transmittance of 82% and steady‐state light yield of 24 600 photons MeV −1 . Moreover, the fast response makes it possible to realize dynamic imaging without ghosting. This work indicates that transparent ceramics provide a new opportunity for high‐quality X‐ray imaging.